The Nursing student profile of a public higher education institution in Amazonas (Research, Society and Development, 2020)
Objective: to trace the demographic and health socioeconomic profile of those entering the nursing course at a public higher education institution. Method: cross-sectional, descriptive, exploratory, quantitative study. The methodological procedures took place in two moments: in the first moment the data collection was made through the questionnaire, in the second moment the vaccine card was analyzed, followed by the measurement of the anthropometric measures, in order to collect information that compose the Index of Body Mass. Results: the profile of the freshman in the nursing course is, mostly, young adolescents, female, aged between 17 and 20 years, single, Christians, coming from the capital, with their own home and living with family members. They have no work or paid occupation. They have outdated vaccination cards and the body mass index classified as normal, even if they are not practicing physical activity. Conclusion: this research provided relevant information for teaching management, in order to know the profile of students, allowing the creation of educational measures and policies that help students in their training.